How Common Is Commercial Contract Cheating in Higher Education and Is It Increasing? A Systematic Review - Newton, Philip M. (Frontiers in Education, 2018)
Contract cheating, where students recruit a third party to undertake their assignments, is frequently reported to be increasing, presenting a threat to academic standards and quality. Many incidents involve payment of the third party, often a so-called “Essay Mill,” giving contract cheating a commercial aspect. This study synthesized findings from prior research to try and determine how common commercial contract cheating is in Higher Education, and test whether it is increasing. It also sought to evaluate the quality of the research evidence which addresses those questions. Seventy-one samples were identified from 65 studies, going back to 1978. These included 54,514 participants. Contract cheating was self-reported by a historic average of 3.52% of students. The data indicate that contract cheating is increasing; in samples from 2014 to present the percentage of students admitting to paying someone else to undertake their work was 15.7%, potentially representing 31 million students around the world. A significant positive relationship was found between time and the percentage of students admitting to contract cheating. This increase may be due to an overall increase in self-reported cheating generally, rather than contract cheating specifically. Most samples were collected using designs which makes it likely that commercial contract cheating is under-reported, for example using convenience sampling, with a very low response rate and without guarantees of anonymity for participants. Recommendations are made for future studies on academic integrity and contract cheating specifically.